59.9k views
2 votes
Combine like terms to create an equivalent expression 3.4 - 2.8d + 2.8d - 1.3

2 Answers

2 votes

Answer:

2.1

Explanation:

i did it on khan and got it right trust me

User Robert Langdon
by
5.1k points
2 votes

Answer:

3.4 - 2.8d + 2.8d - 1.3 = 2.1

Explanation:

The given expression is 3.4 -2.8d + 2.8d -1.3

Let's see the definition of like terms.

Like terms are the terms having the same variable and the same exponents.

Examples: -3xy, 2xy and 4y, 5y and -3, 2.

Now let's identify the like terms from the given expression.

3.4 -2.8d + 2.8d -1.3

Here the like terms are -2.8d, +2.8d and 3.4, -1.3

3.4 -2.8d + 2.8d -1.3

= -2.8d + 2.8d + 3.4 - 1.3 [-2.8d + 2.8d = 0] and 3.4 -1.3 = 2.1

= 0 + 2.1

=2.1

The answer is 2.1

User Ziik
by
6.4k points